Assessment of the Communication Strategies in Reducing Gender-Based Violence among Selected Interventions in Makurdi Area, Benue State - Chile, Martha Fashimaiter (African Journal of Stability and Development (AJSD), 2025)
Gender-Based Violence (GBV) remains a pervasive social and public health challenge in Nigeria, with patriarchal norms, cultural practices, and systemic inequalities perpetuating abuse across communities. This study examined the role of communication strategies in addressing GBV, focusing on the context of Makurdi, Nigeria. The rationale for the research stemmed from the recognition that effective communication is central not only to raising awareness but also to challenging entrenched gender norms and influencing behavioural intentions, evidence on context-specific interventions remained fragmented. Employing a conceptual, descriptive, and analytical design, the study relied exclusively on hypothetical secondary data drawn from peer-reviewed journal articles, government policy documents, NGO and donor agency reports, media campaigns, and theoretical texts. The analysis employed thematic interpretation, logical reasoning, and comparative assessment to evaluate the effectiveness, limitations, and applicability of various communication approaches. Findings revealed that mass media campaigns, interpersonal communication, participatory dialogue, community mobilisation, and digital platforms significantly contributed to awareness creation and normative change. However, deeply embedded patriarchal attitudes, cultural resistance, literacy gaps, and inconsistent media reach constrained the full impact of these interventions. The study highlighted that communication strategies must be culturally tailored, survivor-centred, and multi-channel, integrating both traditional and digital platforms to achieve sustainable behavioural change. Implications suggested that strategic messaging, community engagement, and participatory approaches with youths, men, and opinion leaders were essential for reducing GBV. Overall, the study demonstrated that communication, when theoretically informed and contextually grounded, could serve as a transformative tool in reshaping gender norms, empowering survivors, and complementing broader GBV prevention and policy reforms in Nigeria.